Plant Raf-like kinases regulate the mRNA population upstream of ABA-unresponsive SnRK2 kinases under drought stress - Fumiyuki Soma (Nature Portfolio, 2020)
SnRK2 protein kinases play key roles in signaling during plant responses to abiotic stress. Here Soma et al. report three Arabidopsis Raf-like MAP kinase kinase kinases phosphorylate and activate a subclass of SnRK2s that rapidly respond to osmotic stress independently of ABA signaling.